DIGITAL CITIZENSHIP IN THE NEOSANTARA CONTEXT: A PEDAGOGICAL APPROACH FOR HYBRID LEARNING ENVIRONMENTS - Sara Hussain; Ahmed Shah; Usman Tariq (Journal Neosantara Hybrid Learning, 2026)
The rapid expansion of hybrid learning environments in Southeast Asia has intensified the need for culturally grounded approaches to digital citizenship education. Most existing digital citizenship models originate from Western contexts that prioritize individual autonomy, overlooking the collective ethics and cultural values embedded in Southeast Asian societies. The Neosantara framework, rooted in the integration of local wisdom (Nusantara) with global digital ethics, offers a culturally responsive pathway for nurturing ethical, responsible, and empathetic digital learners. This study aims to examine how Neosantara-based pedagogy fosters digital citizenship within hybrid learning settings by aligning moral education, technological fluency, and cultural identity. A qualitative multiple-case study design was employed across three hybrid schools in Indonesia and Malaysia, involving 30 participants, including teachers, students, and curriculum developers. Data were collected through interviews, classroom observations, and document analysis, then analyzed thematically using a constructivist approach. The findings revealed that integrating Neosantara principles—such as gotong royong (mutual cooperation), tanggung jawab (responsibility), and santun digital (digital courtesy)—enhanced students’ digital ethics, collaboration, and cultural empathy. Statistical analysis supported these qualitative insights, with significant improvements in digital ethics awareness (M = 4.36) and cultural integration (M = 4.45). The study concludes that embedding Neosantara cultural ethics into hybrid learning fosters holistic digital citizenship that balances global digital competence with local moral grounding. The Neosantara Pedagogical Framework provides a replicable model for developing culturally sustainable and ethically resilient hybrid education across Southeast Asia.